Development of Assistive Media for Passing Volleyball for FIK UNIMED Students - Agung Achmadi Lumban Tobing; Sanusi Hasibuan; M. Irfan; Indrakasih Indrakasih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The main objective of this research is developing a medium for assisting passing over as a volleyball learning media. This research was conducted at FIK State University of Medan in 2021. Research at FIK UNIMED Medan will be carried out from February 9 to March 4, 2021. The type of research used is research and development, a small trial sample of 6 students and a large trial of 10 students as well as media, sports and language experts. In small group trialsvalidated by 3 experts, where the percentage of validity reaches 82% - 94.11% with valid criteria can be used. In large group trials the percentage of validity reaches 90% - 98.88%with valid criteria can be used.The small group trial sample of 6 PKO FIK UNIMED students reached 80% with valid criteria, and the large group trial sample of 10 PKO FIK UNIMED students reached 88% with valid criteria. From the test of the effectiveness and efficiency of the passing over aids with learning media experts, it reached 98.18% with valid criteria for use and sports experts reached 96.36% with valid criteria for use. On the basis of the data obtained, the development of the passing-over aids media product is deemed feasible to be developed as one of the learning media aids in volleyball game material.